The impact of respect for employees on the relationship between participative leadership and job satisfaction [electronic resource] - Jomana Salah Salah Aziz, 1983-; Ishak Mad Shah, supervisor; Fakulti Pengurusan (2013)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2013